The Fulfillment of Women's Rights in Verstek Decisions at Samarinda and Sangatta Religious Court - Yuni, Lilik Andar; Kasuma, Jati (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study examines the progressivity of judges in deciding cases without the presence of the litigants (Verstek) which is linked to the fulfillment of women's rights in the Samarinda Religious Court and the Sagata Religious Court. This is because almost 80% of divorce case trials in the Religious Courts are not attended by the parties; So the case was decided by the judge through Verstek. This study was conducted to find out the influence of a Judge's progressivity on protecting the rights of women (wives) after divorcing their husbands. This research is a documentation study carried out by examining several Judges' decisions which were decided in Verstek both in cases of talaq divorce (divorce filed under the will of the husband) and contested divorce (divorce filed under the will of the wife). This study was carried out by using a case study approach combined with a legal study approach; while in the analysis stage, the author uses qualitative descriptive analysis methods. The results of the research conclude that in Verstek decisions the judges tend to be progressive in accommodating women's rights after divorce, both in cases of Talak divorce and contested divorce.